Sociology of Consumption under the Context of Actionist Paradigm - ГлухихАлена Юрьевна (Journal of Economic Sociology, 2010)
The paper represents the author’s position on theoretical and practical research potential of the category “life style” in order to investigate consumers’ behavior. The starting point is the assumption about relative equivalence of culture understood as behavior technology and consumption considered under the context of behavioral practices. The application of actionist paradigm let us formulate the concept of life style which reflects real behavioral actions, fixes their diversity, takes into account institutional restrictions, describes the processes of intention development and finally puts an individual into actor responsible for his/her actions but not into lifeless robot that follows the external conditions without thinking.